2020
DOI: 10.3390/jrfm13040068
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficiency of Canadian Banks: A Three-Stage Network Bootstrap DEA

Abstract: In this study, we focus on how banks can enhance their efficiency in the utilization of resources to ensure their economic sustainability. We propose a novel three-stage (production, investment, and revenue generation) network Data Envelopment Analysis (DEA) with bootstrapping to evaluate the performance of the six big Canadian banks for the period 2000-2017, amid the 2007 financial crisis and the increasing competition level due to new technologies. We identify the best practices in each stage that can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Tsolas (2020) measured performance differences between 62 precious metal mutual funds using weighted additive data envelopment analysis (DEA). Other authors like Dia et al (2020), Neves et al (2020), and Qayyum and Riaz (2018) used DEA for benchmarking and performance measurement in the banking sector in various ways, which proved the applicability of this approach. Horváthová et al (2021) used DEA for benchmarking and performance measurement to provide necessary information for improving business performance.…”
Section: Introductionmentioning
confidence: 80%
“…Tsolas (2020) measured performance differences between 62 precious metal mutual funds using weighted additive data envelopment analysis (DEA). Other authors like Dia et al (2020), Neves et al (2020), and Qayyum and Riaz (2018) used DEA for benchmarking and performance measurement in the banking sector in various ways, which proved the applicability of this approach. Horváthová et al (2021) used DEA for benchmarking and performance measurement to provide necessary information for improving business performance.…”
Section: Introductionmentioning
confidence: 80%
“…Unfortunately, not for the two-stage framework adopted in this study. Because defining deposits as an intermediate variable, in its most general form, requires a flow where bank resources turn into deposits and then deposits turn into investments and loans (see Fukuyama and Weber, 2010;Fukuyama and Matousek, 2011;Degl'Innocenti et al, 2017;Dia et al, 2020).…”
Section: Sample Data and Variablesmentioning
confidence: 99%
“…The results of the BDEA approach applied to a sample of Vietnamese banks in the period 1999-2009 indicate that large and very large banks are more efficient than small and medium-sized banks, with small banks having the lowest efficiency scores in the system; non-state-owned commercial banks are more efficient than state-owned commercial banks in terms of overall efficiency (Stewart et al 2016). Network BDEA and the black box DEA were used on a sample of six big Canadian banks for the period 2000-2017 in order to examine which of the two models provided more accurate results on how the 2007 financial crisis and the increasing competition level due to new technologies affected efficiency [15]. The results indicated that the 2007 financial crisis resulted in lower performance efficiencies.…”
Section: Literature Overviewmentioning
confidence: 99%
“…However, this decline was not substantial for the production and investment stages when the revenue generation stage experienced the largest impact. A comparison of BDEA with the black box DEA model concluded that the network BDEA provides more insightful and accurate results in terms of banks' efficiencies [15]. Samad [16] obtained overall bias-corrected technical efficiency (OTEBC), bias-corrected pure technical efficiency (PTEBC) and biascorrected scale efficiency (SE) of the Islamic banks of the Gulf Cooperating Countries (GCC) during 2014-2016 using the Simar and Wilson [17] BDEA.…”
Section: Literature Overviewmentioning
confidence: 99%